Pengaruh Biostimulan terhadap Intensitas Powderymildew pada Labu Kuning di Desa Tanjung Pering, Kabupaten OganIlir - Afifah, Miftah; Nisa, Nabila Aulia; Lisdiana, Lisdiana; Suwandi, Suwandi; Muslim, A.; Arsi, Arsi; Gunawan, Bambang; Irsan, Chandra; Pratama, Rahmat (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Afifah, M., Nisa.N.A., Lisdiana, L., Suwandi, S., Muslim,A., Arsi, A., Gunawan, B., Irsan, C., & Pratama, R. (2023). Impact of biostimulants on the intensity of powderymildew disease in yellow pumpkin in Tanjung Pering Village, OganIlir Regency. In : Herlinda S et al.(Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp.285-297).Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pumpkin (Cucurbita moschata D.) can be used for various food preparations and contains high carotenoids. But now pumpkin production has decreased by 40% per year due to powdery mildew (Eryshipe cichoracearum). Symptoms of powdery mildew disease are marked white spots on the surface of the pumpkin leaves like flour. Biostimulants are believed to affect prevention of disease and pest attacks in the field. Purpose of this study was to determine the effect of biostimulants on the intensity of powdery mildew attacks on pumpkin and pest attacks. Research selected vegetative phase, observations made in the morning with the calculation of the percentage of powdery mildew disease using Natawigena formulation. There are 4 treatments, namely control, WB , RL and RL+WB , each treatment is 10 repetitions, 4x applications with a frequency of 1x a week, 5X observations.Results of the 2nd week the intensity of the disease increased due to rain after application with moist environmental conditions that support the growth of fungi. The effect of the 3 biostimulant treatments, can reduce the intensity of powdery mildew on pumpkin, was proven on the 3rd to 5th week, which is according to the data % severity of powdery mildew disease always decreases with a percentage of control that continues to increase. The percentage of influence of the greatest effectiveness in the treatment of WB, which is 95% powdery mildew and 2% Aulachopora similis pest control. In the application should see the weather conditions, so that the biostimulant applied can be optimally affected.